PP.06.36: PULSE PRESSURE AMPLIFICATION AND ITS DETERMINANTS ACROSS THE BP SPECTRUM. (June 2015) - Pichler, G.; Martinez, F.; Solaz, E.; Vicente, J.; Calaforra, O.; Ruiz, A.; Lozano, J.; Redon, J.
Abstract : Objective: PP amplification is an independent risk factor for cardiovascular mortality. The aim of this study was to investigate the relationship between PP amplification and Augmentation Index (AIx) in subjects with a broad spectrum of BP values, from optimal BP to HTN grade III. Design and method: Patients attending the HTN Unit of the Clinical Hospital of Valencia were included. Central BP, AIx and augmentation pressure (AP) were assessed using the SphygmoCor device (Atcor medical, Sydney, Australia). PP amplification was defined as ratio between peripheral and central PP. Study participants were divided in groups according to BP values. ANCOVA, Cuzick's test for trend, partial correlation and multiple linear regression models were used for statistical analysis Data were adjusted for age, gender, HR and height. Results: 741 patients (48% women; mean age 53.2 ± 13.6 years; 343 hypertensives (46%); optimal BP n = 123 (17%), normal BP n = 125 (17%), high normal BP n = 150 (20%), HTN grade I n = 245 (33%), HTN grade II n = 73 (10%), HTN grade III n = 25 (3%)). PP amplification was higher in normotensives than in hypertensives (1.31 y 1.28 respectively, p < 0.001). Likewise, a significant difference in PP amplification among BP groups was found (PP amplification 1.33, 1.3, 1.31, 1.29, 1.27 y 1.25 for optimal BP, normal BP, high normal BP, HTN grade I, HTN grade II, HTN grade III, respectively, p = 0.001). AIx and AP were higher with rising BP values. PP amplification showed significant correlation with AIx, AP and BP (r = -0.77, -0.47 and -0.12, respectively, p < 0.001). Main determinants of PP amplification were female sex, age, HR, systolic BP (beta = -0.35, -0.39, 0.53, -0.09, respectively, p < 0.001) and cholesterol (beta = -0.58, p = 0.022). BMI, BP treatment and presence of DM type 2 were not significant. Main determinants of AIx were female sex, age, HR, systolic BP and cholesterol. Conclusions: PP amplification is related to BP categories, the higher the BP the lower the PP amplification and an inverse relationship were observed with AIx and AP after adjusting for covariates. Female sex, age, systolic BP, HR and cholesterol are the main determinants of PP amplification.